Narrative display of the ‘I’ through the visualization of narrative graphs: the case of four women who lost their spouse due to unexpected death - Castillo Ospina, Jennifer; Losada Medina, Margarita Rosa (AWARI, 2021)
This article aims to understand the reconstruction of the self in the grieving process through the unfolding narrative of the stories of four women who lost their spouses due to unexpected death. The applied research technique was the semi-structured interview. For the visualization strategy, narrative graphs were used, and a content analysis was also performed. It was possible to identify and understand the transformation of the self in a narrated timeline by the subjects in which two fundamental folds are formed in this resignification. The first fundamental fold: confrontation and couple relationship; and the second: withdrawal of the couple's relationship and reworking of life as a couple. It was concluded that there are dominant issues regarding death, mourning, and through the narrative technique. It was achievable to elaborate alternative stories by recognizing the meaning that the interviewees gave to loss and the elements of the social and cultural environment present in the grieving process as a relational act, rather than an internal process.